Intelligent Healthcare System Using Patients Confidential Data Communication in Electrocardiogram Signals - Zhao, Ming; Chen, Shuo-Tsung; Chen, Tzu-Li; Tu, Shu-Yi; Yeh, Cheng-Ta; Lin, Fang-Yu; Lu, Hao-Chun (Frontiers in Aging Neuroscience, 2022)
With the advent of the aging era, health care and elderly care have become the focus of medical care, especially the care of the elderly with dementia. Patients confidential data hiding is an useful technology for health care and patient information privacy. In this study, we implement an intelligent healthcare system using the multiple-coefficient quantization technology in transform domain to hide patients confidential data into Electrocardiogram (ECG) signals obtained by ECG sensor module. In embedding patient confidential data, we first consider a nonlinear model for optimizing the quality of the embedded ECG signals. Next, we apply simulated annealing (SA) to solve the nonlinear model so as to have good signal-to-noise ratio (SNR)、RMSE, and rRMSE. Accordingly, the distortion of the PQRST complexes and the ECG amplitude is very small so that the embedded confidential data can satisfy the requirements of physiological diagnostics. In end devices, one can receive the ECG signals with the embedded confidential data and without the original ECG signals. Experimental results confirm the effectiveness that our method remains high quality for each ECG signal with the embedded confidential data no matter how the quantization size Q is increased.